Peningkatan literasi keuanga Melalui Pelatihan Pencatatan Kuangan Digital Dengan Aplikasi SEPRAN pada UMKM Warung Desa Prima Bumijo dan TeachnoLaundry - Martinus Budiantara; Dita Efira Safitri Sri Molah (LPPI UMN AL WASHLIYAH, 2025)
Abstract This Field Work Practice (PKL) activity aims to improve financial literacy among micro business owners through digital financial record training using the SEPRAN application. The activity was conducted at Warung Desa Prima Bumijo and TechnoLaundry, which are community-based business units. This program was motivated by the low level of financial management skills among small business owners, particularly in keeping accurate and organized financial records. Such limitations often lead to difficulties in monitoring cash flow and distinguishing personal from business finances.The implementation methods included initial observation, basic financial literacy education, demonstration of SEPRAN application usage, and hands-on assistance for participants. The SEPRAN application was chosen because of its user-friendly features that enable users to record income, expenses, and generate financial reports automatically.The results of this activity show that the training effectively enhanced participants’ understanding of the importance of digital financial record-keeping. Participants were able to use the SEPRAN application to record daily transactions, monitor profit and loss, and manage their business finances more systematically. Therefore, this program contributes positively to improving financial literacy and efficiency in financial management among MSMEs at Warung Desa Prima Bumijo and TechnoLaundry. Keywords: Financial Literacy, MSMEs, Digital Financial Record, SEPRAN Application